Improve security of wireless sensor networks through reluctant checksum - Qiong Zhang; Jianyu Xiao (International Journal of Distributed Sensor Networks)
The open wireless channel makes the data prone to being eavesdropped. Current wireless security schemes are designed to protect data through cryptography. But an adversary can still recover the secrets by eavesdropping the frames and performing off-line brute-force attacks. Capturing valid frames is fundamental for such attacks. It is generally accepted that each frame at data link layer is designed to include cyclic redundancy check (CRC) checksum sequence for integrity check. However, frame checksum sequence also helps adversary to capture correct frames and drop corrupted ones, which are fundamental to future off-line attacks. In this article, we argue that from the perspective of wireless security, it is unreasonable to include checksum sequence in data link layer frame without any protection. A reluctant checksum scheme named R-CS is proposed. Based on the inherent characteristic of wireless networks that frame error is inevitable, checksum of frame is protected by accumulated checksum algorithm in R-CS. The checksum of the frame cannot be decoded by any nodes except the receiver. Without checksum, adversaries cannot distinguish error frames from correct ones. R-CS requires little computation and communication resources, which is particularly suitable for resource-limited wireless sensor network. Our experimental results clearly demonstrate that R-CS is feasible for wireless sensor network.